2019
DOI: 10.1186/s12918-019-0680-4
|View full text |Cite|
|
Sign up to set email alerts
|

miRNAs and target genes in the blood as biomarkers for the early diagnosis of Parkinson’s disease

Abstract: BackgroundParkinson’s disease (PD) is the second most common neurodegenerative disease, and it is a multifactorial disease with no definite diagnostic index. The aim of this study is to construct a molecular network to find molecules that play important roles in the progression of PD with the goal of using them diagnostically and for early intervention.ResultsWe downloaded two gene expression profiles (GSE54536 and GSE100054) from the Expression Omnibus (GEO) database to analyze possible markers. The Genes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…We also observed a systematic decline in miRNA expression over time, revealing a signature of miRNAs associated with leukocytes, in particular monocytes and B cells, as well as exosomes and RBCs. Among these are several members of the miR-19 and miR-29 families that are consistent with earlier findings [33][34][35][36][37] . Also, PD induced changes for both monocyte and exosome expression signatures has been reported in several other studies [38][39][40][41] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also observed a systematic decline in miRNA expression over time, revealing a signature of miRNAs associated with leukocytes, in particular monocytes and B cells, as well as exosomes and RBCs. Among these are several members of the miR-19 and miR-29 families that are consistent with earlier findings [33][34][35][36][37] . Also, PD induced changes for both monocyte and exosome expression signatures has been reported in several other studies [38][39][40][41] .…”
Section: Discussionsupporting
confidence: 91%
“…Surprisingly, miRNA expression signatures distinguish between iPD and genetic PD, for which effects between disease and controls were largest for iPD. The observed down-regulation of miR-15b-5p is in line with a proposed signature of 5 serum miRNAs in PD patients 32 and a miRNA-mRNA interaction network analysis of PD progression 33 . We also observed a systematic decline in miRNA expression over time, revealing a signature of miRNAs associated with leukocytes, in particular monocytes and B cells, as well as exosomes and RBCs.…”
Section: Discussionsupporting
confidence: 84%
“…EV-cargo was assessed for deiminated proteins as well as for three key microRNAs known to contribute to inflammation and hypoxia (miR21, miR155, and miR210), all of which have also been associated to neurodegenerative diseases and PD [23][24][25], but have not been related to, or assessed in, pre-motor PD before the current study. Epigenetic mechanisms of PD have indeed received increasing attention, including histone modifications, DNA methylation, as well as microRNA involvement [26,27]. Our findings identify EVs and protein deimination as novel markers in pre-motor stages of PD.…”
Section: Introductionmentioning
confidence: 64%
“…Gap junction and platelet activation were identified in this study as KEGG pathways enriched in deiminated proteins in pre-motor PD plasma EVs. Reduced platelet activation has been described in PD [74] and furthermore a recent study has identified gap junctions and platelet activation as KEGG pathways in early PD [26]. Gap junctions are formed by pannexins and connexins and allow for exchange of ions, second messengers, and small metabolites between adjacent cells [75].…”
Section: Discussionmentioning
confidence: 99%
“…Currently no clinically validated biomarkers for PD monitoring has been identified [62]. However, there are evidences that miRNAs can be associated with PD pathophysiology as well, since they seem to be involved in the disease progression by regulating different PD-related genes [14,[63][64][65].…”
Section: Parkinson's Diseasementioning
confidence: 99%